VISUAL EXPLORATION OF SUNFLOWERS AS THE IDEA OF CREATING PAINTINGS - Hanifa Sa'diyah (Universitas Sarjanawiyata Tamansiswa, 2020)
The aim of this senior commitment is to get to know more about sunflowers such as sunflowers from Indonesia but can flourish in Indonesia, known by different names in Indonesia according to the region, how to live sunflowers, how long it takes , its flower characteristics, and its uniqueness that follows the direction of the sun, and then many lessons can be taken from sunflowers. This makes the author interested in better understanding Sunflowers and Making Sunflowers as the basic idea for making artworks with the theme